Sleep Disturbances and Hip Fractures - Ray, Marks (Journal of Aging Research And Healthcare, 2020)
Hip fractures, which remain highly prevalent among the elderly and produce enormous social and economic costs, have not truly abated in prevalence despite years of research that outlines a multitude of preventable risk factors and intervention programs. This review aimed to examine if sleep disturbances have a bearing on the risk of incurring a hip fracture directly or indirectly, among older adults. The specific aim was to explore and summarize what we know, and how this might inform future research and practice. To this end, PUBMED, Web of Science, Scopus, and Google Scholar data bases were searched to uncover available data representing the topic of sleep in relation to hip fractures among the elderly. Articles of note were scrutinized and summarized in narrative form. Results showed very few studies on the topic prevail, even with no restriction on years examined, and of these, discordant, rather than any solid uniform conclusions prevail. It is concluded there is a need to explore this topic carefully, including both the direct, as well as the indirect impact of sleep that may place an older adult at heightened risk for a fall and hip fracture injury as well as subsequent fractures.
Keywords: Falls; hip fractures; sleep; sleep deprivation; sleep quality; older adults; prevention